Chemical Composition and In Vitro Cytotoxic Activity of Essential Oil of Leaves of Malus domestica Growing in Western Himalaya (India). (29th April 2012) - Walia, Mayanka; Mann, Tavleen S.; Kumar, Dharmesh; Agnihotri, Vijai K.; Singh, Bikram
Abstract : Light pale-colored volatile oil was obtained from fresh leaves of Malus domestica tree, growing in Dhauladhar range of Himalaya (Himachal Pradesh, India), with characteristic eucalyptol dominant fragrance. The oil was found to be a complex mixture of mono-, sesqui-, di-terpenes, phenolics, and aliphatic hydrocarbons. Seventeen compounds accounting for nearly 95.3% of the oil were characterized with the help of capillary GC, GC-MS, and NMR. Major compounds of the oil were characterized as eucalyptol (43.7%), phytol (11.5%), α-farnesene (9.6%), and pentacosane (7.6%). Cytotoxicity of essential oil of leaves of M. domestica was evaluated by sulforhodamine B (SRB) assays. The essential oil of leaves of M. domestica, tested against three cancer cell lines, namely, C-6 (glioma cells), A549 (human lung carcinoma), CHOK1 (Chinese hamster ovary cells), and THP-1 (human acute monocytic leukemia cell). The highest activity showed by essential oil on C-6 cell lines (98.2%) at concentration of 2000 μg/ml compared to control. It is the first paper in literature to exploit the chemical composition and cytotoxic activity of leaves essential oil of M. domestica .